2008
DOI: 10.1080/02841850701777390
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted magnetic resonance imaging in differentiation between the viable and necrotic parts of head and neck tumors

Abstract: Creation of an ADC map is an excellent method for differentiation between the viable and necrotic parts of head and neck tumors. Thus, the ADC map can be used to select the best biopsy site and to detect tumor viability in post-treatment follow-up of patients after radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 14 publications
1
45
0
1
Order By: Relevance
“…This can help to select the biopsy site from the solid part of the lymph nodes. Abdel Razek et al [20] reported that the mean ADC of the viable part (1.17±0.33×10 −3 mm 2 /s) was less than that of the necrotic part of the tumor (2.11±0.58×10 −3 mm 2 /s). Thus, ADC map can differentiate the viable from the necrotic part of head and neck tumors.…”
Section: Discussionmentioning
confidence: 96%
“…This can help to select the biopsy site from the solid part of the lymph nodes. Abdel Razek et al [20] reported that the mean ADC of the viable part (1.17±0.33×10 −3 mm 2 /s) was less than that of the necrotic part of the tumor (2.11±0.58×10 −3 mm 2 /s). Thus, ADC map can differentiate the viable from the necrotic part of head and neck tumors.…”
Section: Discussionmentioning
confidence: 96%
“…With respect to the apparent diffusion coefficient (ADC) as a quantitative biomarker in the field of oncology, several investigators have reported promising results for the characterisation of malignancy as well as the prediction and monitoring of therapeutic responses [22][23][24][25][26][27][28][29]. However, the strength of evidence for the two key hypotheses that pretherapy ADC values may indicate the therapeutic outcome and that changes in ADC values predict clinical outcome is still moderate according to the extensive review by Patterson and coauthors [20].…”
Section: Introductionmentioning
confidence: 95%
“…Wang et al 7 reported that a threshold ADC value of 1.22 ϫ 10 Ϫ3 mm 2 /s for differentiating benign and malignant tumors of the head and neck has 87% accuracy, 84% sensitivity, 91% specificity, 93% positive predictive value, and 78% negative predictive value. Abdel Razek et al 20 reported that the mean ADC value of the viable and necrotic part of the head and neck tumor are 1.17 Ϯ 0.33 ϫ 10 Ϫ3 mm 2 /s and 2.11 Ϯ 0.58 ϫ 10 Ϫ3 mm 2 /s, respectively. False-negative and false-positive results were seen in 5 (17%) of our cases.…”
Section: Fig 7 Posttreatment Changes After Surgery and Radiation Thementioning
confidence: 99%